KARAKTERISTIK FISIK, KIMIA, MIKROBIOLOGI WHEY KEFIR DAN AKTIVITASNYA TERHADAP PENGHAMBATAN ANGIOTENSIN CONVERTING ENZYME (ACE) [Physical, Chemical and Microbiological Characteristics of Whey Kefir and Its Angiotensin Converting Enzyme (ACE) Inhibitory Act - Andi Febrisiantosa; Bagus Priyo Purwanto; Yantyati Widyastuti; Irma Isnafia Arief (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
This study was conducted to evaluate the characteristics of whey-based kefir products and their activity to inhibit the angiotensin converting enzyme (ACE). Kefir was produced by using many types of whey, namely SK: skim milk based kefir (control); WK: gouda cheese whey based kefir; and WKB: commercial whey powder based kefir. The experimental design was a completely randomized design. Each treatment was conducted in triplicates. Kefirs were evaluated for physical and chemical properties (pH, total titratable acidity, viscosity, protein, fat, lactose, and alcohol), microbiological (lactic acid bacteria and yeast) population, peptide concentration, ACE inhibition, IC50 and Inhibition Efficiency Ratio (IER). The results showed that the types of whey used for kefir productions significantly affected the physical and chemical characteristics of the products (p<0.05). Total lactic acid bacteria and yeast population of the products were not significantly different among the whey types (p>0.05). The peptide concentration and ACE inhibitory activity of WK, 1.54±0.02 mg/mL and 73.07±0.91%, was significantly higher (p<0.05) than those of the control and WKB. The IC50 of WK was 0.83±0.02 mg/mL, significantly lower than that of control (1.05±0.01 mg/mL) and WKB (0.96±0.01 mg/mL). The IER of WK (47.35±0.09% per mg/mL) was not significantly different (p>0.05) from the control (47.19±0.09% per mg/mL) but was significantly higher (p<0.05) than that of WKB (45.75±0.18% per mg/mL). This research indicated that whey kefir is a potential source of bioactive peptide for antihypertention agent.